ANALISIS MATERI BUKU “33 HARI MAHIR BAHASA ARAB” KARYA USTADZ H. SYAIFUL ALIM, LC., M.PD. - Ida Purwani; Irvan Iswandi; Moh. Mas` ud Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the content quality of the book 33 Hari Mahir Bahasa Arab written by Ustadz H. Syaiful Alim, Lc., M.Pd., and to evaluate its compliance with W.F. Mackey’s principles of language teaching materials development, namely selection, gradation, presentation, and repetition. This research employed a qualitative approach with a library research design, supported by content analysis and interviews as data collection techniques. The findings reveal that the book generally meets the criteria of a good textbook in terms of content, language, presentation, and graphics. Its strengths lie in the selection of functional materials, the progressive gradation of topics, the simple and communicative presentation, and the consistent application of repetition. However, some weaknesses were also identified, such as limited variation in presentation methods, lack of visual and digital media integration, and insufficient context-based practice tasks. Thus, it can be concluded that the book is suitable as a teaching material for beginner learners, although further development is needed to meet the demands of modern language learning. Keywords: Content analysis, textbook, Arabic language, Mackey’s principles, language learning